Isolated extraocular orbital mass: a rare presentation of sarcoidosis - Sah, Birendra P; Sharma, Bikram; Iannuzzi, Michael C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
We report a case of orbital sarcoidosis in a 66 year old male who presented with one month history of right eye swelling and intermittent diplopia. MRI revealed an enhancing infiltrative soft tissue mass in the inferior aspect of the right orbit and biopsy of the mass demonstrated non-necrotizing granulomas. Chest CT scan was normal and PET scan showed no other organ involvement. He was treated with tapering doses of prednisone over six months. Although relapse occurred while tapering prednisone to 20 mg per day, he responded well to the addition of azathioprine with complete resolution of visual difficulties and orbital the mass on repeat MRI. Sarcoidosis, presenting as an isolated orbital mass is rare, can be successfully treated and should be included in differential diagnosis.